Meningkatkan Kemampuan Berhitung Anak Usia 5-6 Tahun Melalui Permainan Batu Kerikil TK Negeri Pembina 02 Kampar - Mailani Edelwina; Citra Ayu; Lusi Marleni (Jurnal Pendidikan Tuntas, 2024)
The purpose of this research is: to determine the improvement of counting skills of children aged 5-6 years through gravel games at TK Negeri Pembina 02 Kampar. This research method is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely the planning, implementation, observation, and reflection stages. The time of this research was carried out from July to August 2024. The subjects of this study were 5-6 year old children at TK Negeri Pembina 02 Kampar, totalling 15 children. Data collection techniques are documentation, observation and tests. The results of this study indicate that there is an increase in counting ability from the time of pre-action. Children's counting ability at the time of pre-action showed results in the category of still developing (MB) which was shown from the total assessment only reached 47.5% which was included in the category of Still Developing (MB). Meanwhile, the total score of children's counting ability at the second meeting of cycle I was 215 or 67.2%, while the total score of children's counting ability in cycle II was 268 or 83.8% which is included in the Very Well Developed category (BSB). This achievement has been at 83.8% or part of the students who get the predicate of developing very well, so there is no need to take action again through the third cycle.